Employment and development in Asia - Rolph van der Hoeven (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
How have economic development, employment, and labour markets in Asian countries interacted since the publication of Myrdal's Asian Drama? Myrdal rejected, the western approach to and definition of employment and emphasized the role of "informal" employment, but he underestimated the effects of the Lewisian development process. In fast-growing countries with better labour market development, initial conditions have played a role, though less than Myrdal predicted. Myrdal's concept of cumulative causation better explains how fast-growing countries with better labour markets have developed. These countries have pursued a developmental state and applied interventionist policies in agriculture, industry, and macroeconomics, as well as in social policies and in strengthening the position of women in the labour market. Successful countries are also characterized by initial low-income inequality and targeted redistribution of factors of production. For some countries, though, growing inequality together with other development challenges can, if not attended to, become a problem in the future.
Keywords: E6; J21; J24; O15; O25; O4; 330; labour force and employment; economic growth and aggregate productivity; human capital; income distribution; industrial and macroeconomic policy